Development and study of a bifunctional photocatalyst based on SAPO-34 molecular sieve - Wang, Run-quan; Chen, Wan-ping; Zhang, Yue-rong; Song, Kai; Tian, Yuan; Li, Jia-xian; Shi, Gao-feng; Wang, Guo-ying (New journal of chemistry, 2023)
A new bifunctional photocatalyst was constructed from a modified SAPO-34 molecular sieve successfully connected with BiVO 4 crystals through O bridges. The new as-fabricated catalyst not only had enriched active sites of B-acid and L-acid on the surface of the molecular sieve but also enriched active sites of L-acid on the surface of the molecular sieve. The electron-transfer ability between the SAPO-34 molecular sieve and BiVO 4 crystals was improved, and the recombination of electrons and holes in BiVO 4 crystals was inhibited. With the synergistic action of the B-acid and L-acid, the molecular zeolite showed very high activity for the photocatalytic degradation of formaldehyde aqueous solution with a photoreaction rate constant of 0.291 min −1 and degradation rate of 84.34%. Compared with the BiVO 4 crystal, the performance improved 10 times. Based on the calculation of the band structure and state density of the BiVO 4 crystal and the HOMO and LUMO energy levels of the SAPO-34 molecular sieve, a mechanism for the photocatalytic degradation of formaldehyde is proposed and the energy levels of the intermediate products were calculated. This study provides a method for the preparation of composite molecular sieve photocatalysts and a new idea for the construction of bifunctional photocatalysts. A new bifunctional photocatalyst was constructed from a modified SAPO-34 molecular sieve successfully connected with BiVO 4 crystals through O bridges.